Investigating Teachers' Attitudes towards Multicompetence in English Language Teaching - Pertiwi, Isnaini Roro; Basikin, Basikin (International Journal of Contemporary Studies in Education, 2026)
Purpose – This study investigates English tutors’ attitudes toward multicompetence in an English course in Yogyakarta. Multicompetence views language learners as users of multiple linguistic systems rather than imperfect native speakers. Despite its growing relevance in language education, limited research explores how tutors in private language courses perceive this concept. Therefore, this study aims to examine tutors’ perspectives on multicompetence and its relevance to English language learning. Methodology – This study employed a qualitative descriptive research design. Six English tutors from an English course institution in Yogyakarta were selected using purposive sampling. Data were collected through semi-structured interviews to explore tutors’ perceptions of multicompetence. The analysis followed three stages: familiarization with the data, coding, and interpretation. The interview transcripts were analyzed thematically to identify patterns related to teaching perspectives and the use of learners’ first language. Findings – Tutors generally hold positive attitudes toward multicompetence. They emphasize effective communication rather than native-like fluency and consider students’ first language as a valuable learning resource. Tutors also view multilingual ability as an advantage in language learning. The study suggests that integrating multicompetence into teaching can support communicative competence and more inclusive learning environments. Novelty – This study provides insights into tutors’ perceptions of multicompetence within the context of private English language courses. Significance – The findings may benefit English teachers, teacher trainers, language course providers, and researchers by helping develop more inclusive language-teaching practices.